The effects of quercetin on antioxidant system and some blood parameters in rats exposed to acute cadmium toxicity - İhsan Kısadere; Nurcan Dönmez (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to determine the effects of quercetin on antioxidant system and some blood parameters in rats exposed to acute cadmium toxicity. Materials and Methods: Adult male Wistar-Albino rats (n = 30) were used and divided into four groups as Control (C, n = 6), Cadmium (Cd, n = 8), Quercetin (Q, n = 8) and Cadmium + Quercetin (Cd + Q, n = 8). Cadmium chloride (CdCl2, 4 mg/ kg daily, s.c) were administrated to Cd and Cd+Q groups, and Quercetin (Q, 50 mg/kg daily, i.p) were given to Q and Cd + Q groups for 3 days, respectively. Control group was not recieved any treatment. Blood samples were collected from all animals at fourth day after treatments. Results: The levels of serum SOD, MDA, GSH, catalase, and plasma ALT, AST, GGT, total protein, albumin were detected. Although, serum MDA levels were found higher (P< 0.05) in Cd than the other groups, it was similiar in Q and C groups. ALT, AST and GGT enzyme levels were observed higher in Cd than C and Q groups (P< 0.05). Conclusion: Negative effects of acute cadmium toxicity on antioxidan system and some hematological parameters were ameliorated with quercetin treatment in rats.